The utility of routine post-hospitalization CT imaging in patients with non-operative mild to moderate traumatic brain injury. (7th June 2021) - Sadrameli, Saeed S.; Davidov, Vitaliy; Sulhan, Suraj; Vaziri, Sasha; Hartman, Cory J.; Hooten, Kristopher G.; Murad, Gregory J.A.
ABSTRACT: Primary Objective: The purpose of this study was to determine the utility of CT imaging in patients with non-operative mild–moderate TBI with respect to changes in management. Methods: We conducted a retrospective analysis for 191 patients over a 5-year interval to examine whether follow-up CT initiated a change in management. We created a logistic regression model to incorporate different variables contributing to change in management. Results: Of 191 patients, 31 (16.2%) underwent a change in management. Change in management was associated with older age (65 yo vs. 55 yo, p = .011), diagnosis of subdural hematoma (p = .041), antiplatelet/anticoagulant therapy (p = .009), imaging performed (p = .16), and increased blood products on CT (p = <0.0001). For patients on antiplatelet/anticoagulant therapy, only those with worsening findings on CT required a change in management (p = .0002, 0.039). Surgical intervention was indicated in two patients. Conclusions: Limited clinical value exists in repeat CT scans for patients with mild TBI. Most patients with traumatic SAH, contusions, or asymptomatic patients should not have repeat imaging, as our study revealed only 2% of patients with positive CT finding and 0.6% requiring surgical intervention.